STRUKTUR, PERILAKU, DAN KINERJA INDUSTRI PENGOLAHAN MAKANAN DI INDONESIA - Sri Yani Kusumastut; Anna S. N. Dasri (Universitas Mercu Buana, 2015)
Abstract:Global financial crisis has threatened livelihoods and access to food for those who have lost jobs and income. Deteriorating in purchasing power due to decline in income and high inflation, in turn will affect food consumption. This situation undoubtly brings about the disruption in food security. The food security pillar should not rely on quantitative approach, but also on other pillars in a wider food spectrum. The ways to enhance food security is to develop food diversification based on food industry. The aim of this paper is to analyze how the impacts of global financial crisis on food security based on food industry in Indonesia. This research takes 9 groups of 5 digits KBLI code of food industry in 1996-2009 periods. The analyzed method is based on panel data using simultaneous equation model. The result shows that there is a simultaneous relation between structure conduct and performance of food industry and food security. Market structure of food industry become more concentrated in that period and GFC affected market concentration on some KBLI of food industry.Keywords: food industry, food security, structure-conduct-performance